MUSIC IN MALVI FOLK SONGS: मालवी लोकगीतों में संगीत - Bhatt Saxena, Archana (International Journal of Research -GRANTHAALAYAH, 2015)
Indian folk life has always been music. There is no caste in India which does not have any influence on music. For Indian music, it is said that knowledge of Brahm comes from literature and Brahm is obtained from music. In India, there has been a tradition of singing, playing and dancing on various festivals and occasions since ancient times. Folklore is the indelible boon of ancient culture and wealth in which the souls of many cultures have been united. Folk music is a joyous expression of public life. According to Padma Shri Omkaranath- Folk music is the background to the development of Devi music. The country or caste of which a sensitive human was oriented to express the feelings of his heart, on the same occasion, the self-proclaimed tone, rhythm, nature emerged from his mouth and the classical development which he developed by binding the same tone, song and rhythm Gaya became the only country music. भारतीय लोक जीवन सदैव संगीत मय रहा है। भारत वर्ष का कोई अंचल कोई जाति ऐसी नहीं जिसके जीवन पर संगीत का प्रभाव न पड़ा हो। भारतीय संगीत के लिए कहा जाता है कि साहित्य से ब्रह्म का ज्ञान और संगीत से ब्रह्न की प्राप्ति होती है। भारत में पुरातन काल से विभिन्न पर्वो एवं अवसरों पर गायन, वादन व नृत्य की परंपरा रही है। लोकगीत प्राचीन संस्कृति एवं सम्पदा के अमिट वरदान है जिसमें अनेकानेक संस्कृतियों की आत्माओं का एकीकरण हुआ है। लोक संगीत जन-जीवन की उल्लासमय अभिव्यक्ति है। पद्म श्री ओंकारनाथ के मतानुसार- ‘‘देवी संगीत के विकास की पृष्ठभूमि लोक संगीत है। जिस देष या जाति का सम्वेदनषील मानव जिस समय अपने हृदय के भावों को अभिव्यक्त करने के लिए उन्मुख हुआ उसी अवसर पर स्वयंभू स्वर, लय, प्रकृत्या उनके मुख से उद्भूत हुए और उन्हीं स्वर, गीत और लय को नियम बद्ध कर उनका जो शास्त्रीय विकास किया गया वही देषी संगीत बना।‘‘